Slovenska književnost v italijanskih antologijah jugoslovanskih književnosti po letu 1945 - Jan, Zoltan (Jezik in slovstvo, 1999)
A substantial part of Italian translations of Slovene literature published in book form has appeard in anthologies is reviewed, as well as the circumstances in which the anthologies were published. The rich network of ties among individuals behind the publishing of Slovene literature in Italy is explained, together with the background of various polemical debates aroused by the publication of the anthologies. After calling attention to several more modest and less known presentations of Slovene literature as part Yugoslav literature in Italian thematic anthologies of world literature, the author dicousses the consequences of this presentation of Slovene literature within the framework of Yugoslav literature.
Keywords: Slovene literature; slovenska književnost; prevodi; Italian; italijanščina; antologije